Programma Openlucht Theater Vondelpark: 21 juli: Wally Shortz & Neppie Noya, Protheater; 22 juli L&H Band; 23 juli Damesorkest 'Het Salon'; 24 juli: Los Locos Normalos, One World Poetry; 25 juli: Pigeondrop, Fernando's Ginga, Paolo Passionato & The Pennies from Heaven (1982)
Programma Openlucht Theater Vondelpark: 21 juli: Wally Shortz & Neppie Noya, Protheater; 22 juli L&H Band; 23 juli Damesorkest 'Het Salon'; 24 juli: Los Locos Normalos, One World Poetry; 25 juli: Pigeondrop, Fernando's Ginga, Paolo Passionato & The Pennies from Heaven.